Travel cost adjustment of international multiple destination visitors to the Kilim Karst Geoforest Park, Langkawi, Malaysia - Matthew, Nitanan Koshy; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (Institut Kajian Dasar Pertanian dan Makanan, Universiti Putra Malaysia, 2015)
Kilim Karst Geoforest Park (KKGP) located in Langkawi island offers pristine nature based attractions to visitors. Apart from local visitors, the park receives many international visitor arrivals from all over the world. The demand model of international visitors to the park can be developed using one of the common environmental valuation techniques, the Travel Cost Method (TCM). And, using the demand curve, the benefit obtained by the international visitors to the park can be estimated using the concept of consumer surplus. In this research, Individual Travel Cost Model (ITCM) has been employed. One of the common issues in travel cost studies is to obtain the specific travel cost attributable to the specific location for multiple destination visitors. In regards to that, travel cost and consumer surplus adjustment techniques are among the popular techniques to determine the cost. Thus, the article determines the consumer surplus value of international visitors from the travel cost adjustment. Structured questionnaire and face-to-face data collection method are employed to obtain the primary data from 330 international visitors using the purposive sampling technique. The analysis using the Poisson regression shows that the travel cost, time cost, quality of site, age and education variables, are significant at 95% level of confidence. Hence, the average consumer surplus value per person/trip/year is estimated to be €216/RM 864, whilst the total consumer surplus value is estimated to be (€27 million/RM 108 million). It is hoped that the findings from this study could provide useful information to the Langkawi Development Authority (LADA) pertinent to the management of the park.